The dialectical relationship between the organization's growth and its value under the framework of the diversification strategy - حمود, سعد علي; اسماعيل, مصطفى منير (Journal of Economics and Administrative Sciences, 2010)
The research is conducted on target of investigating the role of growth strategy via diversification in value maximization of a firm in terms of controversies literatures had witnessed. Using a descriptive approach for analyzing and verifying the harmony of variables of research and their conceptualized logic , it could be reached to many conclusions agreed in their essence upon that the related diversification has the major role in value maximization of a firm and the wealth of its owners .